Forest Microhabitat Affects Succession of Fungal Communities on Decomposing Fine Tree Roots - Kohout, Petr; Sudová, Radka; Brabcová, Vendula; Vosolsobě, Stanislav; Baldrian, Petr; Albrechtová, Jana (Frontiers in Microbiology, 2021)
Belowground litter derived from tree roots has been shown as a principal source of soil organic matter in coniferous forests. Fate of tree root necromass depends on fungal communities developing on the decaying roots. Local environmental conditions which affect composition of tree root mycobiome may also influence fungal communities developing on decaying tree roots. Here, we assessed fungal communities associated with decaying roots of Picea abies decomposing in three microhabitats: soil with no vegetation, soil with ericoid shrubs cover and P. abies deadwood, for a 2-year period. While forest microhabitat did not affect composition of fungal communities associated with living roots, we found significant differences in composition of fungal communities on decaying roots. Some ericoid mycorrhizal fungi showed higher relative abundance on decaying roots in soils under ericoid shrub cover, while saprotrophic fungi had higher relative abundance in roots decomposing inside deadwood. Regardless of the studied microhabitat, we observed decline of ectomycorrhizal fungi and increase of endophytic fungi during root decomposition. Interestingly, we found substantially more fungal taxa with unknown ecology in late stages of root decomposition, indicating that highly decomposed roots may represent so far overlooked niche for soil fungi. Our study shows the importance of microhabitats on the fate of the decomposing spruce roots.